Reactors antineutrino anomalies and searches for sterile neutrinos. (8th April 2015) - Cribier, M
Abstract: Over the last 20 years a standard neutrino oscillation framework associated with small splitting between the neutrino mass states have become well established. Beyond this model, anomalies have been observed at short baseline in reactor, accelerator and gallium experiments. This suggests the existence of a fourth massive neutrino, affecting experiments through oscillation with active flavours with Δm 2 above 0.1 eV 2 . To definitively test this Δm 2 region, several experiments on reactors or using neutrino or antineutrino sources are in preparation.